Merdeka Belajar dan Pendidikan Islam dalam Membangun Generasi Cerdas dan Berkarakter di Era Digital - Zainudin, Zainudin (Jurnal el-Huda, 2024)
Independent learning is an education policy that aims to provide students with the freedom to choose learning methods and methods that suit their interests and needs. This policy aims to create an education system that is more flexible, creative, and relevant to the challenges of the times. From the perspective of Islamic education, Independent learning does not only focus on academic achievement, but also on developing a strong character, which is in accordance with Islamic values. Islamic education emphasizes the importance of a balance between knowledge (useful knowledge) and morals (noble character), so that students are not only intelligent, but also have noble character. In the rapidly developing digital era, young generations face major challenges, both in terms of very broad access to information and the negative impacts of technology. Therefore, Islamic education has an important role in guiding students to become wise and responsible users of technology. With the Independent learning approach, it is hoped that a generation can be created that is intelligent, has character, and is able to face global challenges by prioritizing moral and spiritual values.